2013
DOI: 10.1007/s10334-013-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct cerebral and cardiac 17O-MRI at 3 Tesla: initial results at natural abundance

Abstract: Cerebral and cardiac (17)O-MRI at natural abundance is feasible at 3 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…). Cardiac 17 O‐imaging has also been demonstrated . Recently, the focus was shifted towards an improvement of the prior knowledge input in the metabolism model and iterative reconstruction with PVC…”
Section: Current State and Technical Challengesmentioning
confidence: 99%
“…). Cardiac 17 O‐imaging has also been demonstrated . Recently, the focus was shifted towards an improvement of the prior knowledge input in the metabolism model and iterative reconstruction with PVC…”
Section: Current State and Technical Challengesmentioning
confidence: 99%
“…It can be assumed to be linearly correlated with the concentration of 17 O due to the short relaxation times (26,37,49 O concentration in mmol per gram tissue, the 17 O signal intensities before gas inhalation (i.e., during the baseline phase) were normalized using the H 2 17 O natural abundance of 20.56 mmol/g water , water partition coefficients [0.71 g/mL for WM and 0.83 g/mL for GM (50)], and averaged density of brain tissue of 1.038 g/mL (51).…”
Section: Cmro 2 Quantification Modelmentioning
confidence: 99%
“…Unfortunately, UHF MR systems are not widely available and are not yet used in clinical routine. Recently, feasibility of direct 17 O MRI in human brain and heart at clinical field strengths of 3T has been reported (37), which has the ultimate goal of implementing CMRO 2 quantification at clinical MR systems. In the previous studies, a rebreathing (RB) system was implemented for efficient usage of rare and expensive 17 O 2 gas by re-inhalation of the stored 17 O 2 gas in subsequent inhalation cycles (27,33).…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of applying the in vivo 17 O MR technique to hearts has been tested in rats at 9.4T [37, 57] and in human hearts at 3T [54]. The preliminary results as displayed in Figure 7 suggest that it is feasible to establish a noninvasive imaging modality with in vivo 17 O MR detection and appropriate quantification modeling for simultaneously imaging the myocardial oxygen metabolic rate (MVO 2 ) and myocardial perfusion [37].…”
Section: Recent Development and Applications Of In Vivo 17o Mrs And Imentioning
confidence: 99%
“…It has been shown that a few millimeter spatial resolution in preclinical studies [26, 34, 35, 37–39, 48, 50, 51] and close to a centimeter in human studies [32, 45, 53] with ~10–15 sec temporal resolution can be reached with B 0 ≥ 7T. Relatively lower resolutions are expected with lower field magnets, e.g., a 3T clinical scanner, or when large volume coils are employed [30, 36, 54, 56]. It is worth mentioning that while 17 O MR benefits from the sensitivity gain at a higher field, it also requires a larger RF power to achieve the same RF pulse flip angle because of its low γ-ratio.…”
Section: Challenges and The Potential Of The In Vivo 17o Mrs And Imagingmentioning
confidence: 99%